Optical frequency domain imaging vs. intravascular ultrasound in percutaneous coronary intervention (OPINION trial): Study protocol for a randomized controlled trial. Issue 5 (November 2016) - Kubo, Takashi; Shinke, Toshiro; Okamura, Takayuki; Hibi, Kiyoshi; Nakazawa, Gaku; Morino, Yoshihiro; Shite, Junya; Fusazaki, Tetsuya; Otake, Hiromasa; Kozuma, Ken; Akasaka, Takashi
Abstract: Background: Optical coherence tomography is becoming increasingly widespread as an adjunctive intravascular diagnostic technique in percutaneous coronary intervention (PCI), because of its ability to visualize coronary structures at high resolution. Several studies have reported that intravascular ultrasound (IVUS) guidance in PCI might be helpful to reduce subsequent stent thrombosis, restenosis, repeat revascularization, myocardial infarction, and cardiac death. The OPtical frequency domain imaging vs. INtravascular ultrasound in percutaneous coronary InterventiON (OPINION) trial is aimed at evaluating the impact of optical frequency domain imaging (OFDI) guidance in PCI on clinical outcomes compared with IVUS guidance. Methods and design: The OPINION trial is a multicenter, prospective, randomized, controlled, open-label, parallel group, non-inferiority trial in Japan. The eligible patients are randomly assigned to receive either OFDI-guided PCI or IVUS-guided PCI. PCI is performed using the biolimus-eluting stent in accordance with a certain criteria of OFDI and IVUS for optimal stent deployment. All patients will undergo a follow-up angiography at 8 months. The primary endpoint is target vessel failure composed of cardiac death, myocardial infarction attributed to the target vessel, and clinically-driven target vessel revascularization at 12 months. Conclusion: When completed, the OPINION trial will contribute to define the clinical value of the OFDI guidance in PCI.